2015
DOI: 10.1007/s11657-015-0217-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting bone mineral density in postmenopausal women

Abstract: The results of this study indicated a significant association between OP and MD, obesity, parity, MS, history of fracture, serum ferritin, level of education, and physical activity. However, the direction and the strength of association varied across BMD measurement sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 28 publications
7
45
2
4
Order By: Relevance
“…The elderly presented high proportions of chronic diseases, which are usually diagnosed before the age of 60. There is other evidence that the presence of chronic diseases such as diabetes, hypertension and dyslipidemia [9], obesity and metabolic syndrome [10] were not associated with low BMD in post-menopause women, but the study presented herein is the first to carry out such evaluation for elderly men.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The elderly presented high proportions of chronic diseases, which are usually diagnosed before the age of 60. There is other evidence that the presence of chronic diseases such as diabetes, hypertension and dyslipidemia [9], obesity and metabolic syndrome [10] were not associated with low BMD in post-menopause women, but the study presented herein is the first to carry out such evaluation for elderly men.…”
Section: Discussionmentioning
confidence: 80%
“…Deficiency in estrogen levels results in lower bone metabolic activity, increasing bone reabsorption and consequently progressive loss of trabecular bone [10,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, a negligible correlation was determined between BMI and BMD values for femoral neck region, but no statistically significant correlation was observed for lumbar region. In a cross-sectional case-control study including 537 postmenopausal women, it was shown that BMI correlated positively with femoral neck and lumbar spine BMD (15). In the community-based study analysis [National Health and Nutrition Examination Survey (NHANES III) in which 2.590 women and 2.391 men between 50-79 years of age were included, the most important and statistically significant risk factors identified were low BMI, low calcium intake, current cigarette smoking, and physical inactivity (16).…”
Section: Discussionmentioning
confidence: 99%